The assessment of childhood maltreatment and its associations with affective symptoms in adulthood: results of the German National Cohort (NAKO) - Klinger-König, Johanna; Streit, Fabian; Erhardt, Angelika; Kleineidam, Luca; Schmiedek, Florian; Schmidt, Börge; Wagner, Michael; Deckert, Jürgen; Rietschel, Marcella; Berger, Klaus; Grabe, Hans J.; Mikolajczyk, Rafael; et al. (The world journal of biological psychiatry, 2023)
Childhood maltreatment affects 20-30% of the German population and is an important risk factor for physical and mental diseases in adult life. This study reports first results of the distribution of childhood maltreatment in the population-based mega cohort German National Cohort (NAKO) and estimates associations with affective symptoms in adulthood. The Childhood Trauma Screener (CTS), a short version of the Childhood Trauma Questionnaire, was used in 83,995 adults (age: 20-72 years; 47.3% men) of NAKO. The five-item CTS assesses the severity of three types of childhood abuse and two types of childhood neglect. Overall, 21,131 participants (27.5%) reported at least one type of childhood maltreatment; 14,017 participants (18.3%) reported exactly one type and 250 participants (0.3%) reported all five types of childhood maltreatment. Small differences regarding age (mean absolute deviation around the mean (MAD)=0.47), sex (MAD = 0.07) and education (MAD = 0.82) were observed. The severity of childhood maltreatment was associated with more severe symptoms of depression (β = 0.23), anxiety (β = 0.21) and perceived stress (β = 0.23) in adulthood, validated particularly for emotional abuse and emotional neglect. The distribution of childhood maltreatment in NAKO is similar to previous reports. Additionally, our results suggest differential associations with psychopathological symptoms for the five types of childhood maltreatment.